Unexplained Loss of Vision in a Child: Consider Bilateral Primary Optic Nerve Sheath Meningioma - Nickel, Miriam; Löbel, Ulrike; Holst, Brigitte; Kammler, Gertrud; Matschke, Jakob; Schulz, Angela; Kohlschütter, Alfried (Neuropediatrics, 2014)
A 4-year-old girl gradually lost her vision to become practically blind at the age of 10 years. Examinations at several medical centers had been unable to establish an etiology. Traditional investigation using cerebral magnetic resonance imaging (MRI) initially showed normal results; however, later on it showed progressive atrophy of both optical nerves without recognizable cause. Subsequently, MRI including adequate orbital sequences, contrast-enhanced sequences, and fat suppression demonstrated bilateral primary optic nerve sheath meningioma, a rare but treatable tumor of childhood. The patient underwent neurosurgery and to date retains minimal vision. Adequate neuroradiological investigation of unexplained optic atrophy is advocated.
Keywords: optic nerve tumor; optic nerve atrophy; bilateral visual loss; child